A Longitudinal Assessment of Associations Between Women's Tendency to Pretend Orgasm, Orgasm Function, and Intercourse-Related Pain in Different Partner Relationship Constellations. - Patrick Jern; Outi Hakala; Antti Kärnä; Annika Gunst (Springer International Publishing AG, 2022)
The aim of the present study was to investigate how women's tendency to pretend orgasm during intercourse is associated with orgasm function and intercourse-related pain, using a longitudinal design where temporal stability and possible causal relationships could be modeled. The study sample consisted of 1421 Finnish women who had participated in large-scale population-based data collections conducted at two time points 7 years apart. Pretending orgasm was assessed for the past 4 weeks, and orgasm function and pain were assessed using the Female Sexual Function Index for the past 4 weeks. Associations were also computed separately in three groups of women based on relationship status. Pretending orgasm was considerably variable over time, with 34% of the women having pretended orgasm a few times or more at least at one time point, and 11% having done so at both time points. Initial bivariate correlations revealed associations between pretending orgasm and orgasm problems within and across time, whereas associations with pain were more ambiguous. However, we found no support in the path model for the leading hypotheses that pretending orgasms would predict pain or orgasm problems over a long period of time, or that pain or orgasm problems would predict pretending orgasm. The strongest predictor of future pretending in our model was previous pretending (R 2 = .14). Relationship status did not seem to affect pretending orgasm in any major way.